KEPEMIMPINAN PENDIDIKAN ISLAM DALAM MENGARUNGI BAHTERAH RUMAH TANGGA - Febrian, Rahmat; Somantri, Fajar; Rahmat, Didis Pauji; Triwijaya, Bariul Ammar (Konsorsium Dosen Sekolah Tinggi Agama Islam (STAI) Al-Yasini Pasuruan, 2020)
Abstract Marriage is a common goal in a couple to get happiness together. but keep in mind that when the marriage is over it is not the end of the existing problems, but the beginning of a new journey without direction, whose compass